The ethics of Al-generated imagery in journalism - Dan Valeriu VOINEA (Social Sciences and Education Research Review)
The rapid advancement of generative artificial intelligence (AI) capable of producing highly realistic images presents profound ethical challenges for journalism. This paper examines the multifaceted ethical landscape surrounding Al-generated imagery in news contexts, synthesizing current scholarship and expert perspectives. It analyzes the significant risks posed by synthetic media, focusing on four key themes